1991
DOI: 10.1007/bf01955534
|View full text |Cite
|
Sign up to set email alerts
|

Low arylsulphatase A activity and choreoathetotic syndrome in three siblings: differentiation of pseudodeficiency from metachromatic leukodystrophy

Abstract: We report on a family with a sibship of three children for whom the diagnosis of "an unusual form of metachromatic leukodystrophy (MLD)" had been suggested earlier. The patients had choreiform movements and dystonic posturing accompanied by dysarthria since childhood. The availability of the polymerase chain reaction enabled us to show that the three siblings have a pseudodeficiency genotype (ASAp/ASAp). There was no abnormal sulphatiduria, and we propose that the neurological disease and low arylsulphatase A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…For example, benign familial chorea, char acterized by childhood o nset and a relatively b e nign co u rse,7 sta n d s in c o n tra st to HD, w hereas d e n ta to -ru b ro -p a llid a l-lu y sia n atro p h y (DRPLA), another autosom al dom inant condition, m ay closely mimic HD.S O ther familial disorders w ith chorea as a prom inent feature have also been described. 9,10 T here are instances of late-onset, nonhereditary ch o rea w ith o u t o th e r neurologic m a n ife sta tio n s d e sig n a te d as senile chorea. Some have a rg u e d th a t senile chorea m ay frequently rep resen t lateonset H D .11 However, HD does not account for all reported cases of senile chorea,12 and there is g e netic evidence for senile chorea being a distinct e n tity from H D .1;U1…”
mentioning
confidence: 97%
“…For example, benign familial chorea, char acterized by childhood o nset and a relatively b e nign co u rse,7 sta n d s in c o n tra st to HD, w hereas d e n ta to -ru b ro -p a llid a l-lu y sia n atro p h y (DRPLA), another autosom al dom inant condition, m ay closely mimic HD.S O ther familial disorders w ith chorea as a prom inent feature have also been described. 9,10 T here are instances of late-onset, nonhereditary ch o rea w ith o u t o th e r neurologic m a n ife sta tio n s d e sig n a te d as senile chorea. Some have a rg u e d th a t senile chorea m ay frequently rep resen t lateonset H D .11 However, HD does not account for all reported cases of senile chorea,12 and there is g e netic evidence for senile chorea being a distinct e n tity from H D .1;U1…”
mentioning
confidence: 97%
“…Pseudodefi ciency o f a lysosomal enzyme is much more frequent than previously thought and may pose a serious diagnos tic problem, particularly for prenatal diagnosis. In Cen tral Europe, approximately 1 in 200 persons is estimated to be homozygous for ASA pseudodeficiency [4] and a large number o f atypical MLD patients with some other,' unrelated neurologic disease are probably misdiagnosed pseudodeficient probands [5,6].…”
Section: ) [2]mentioning
confidence: 99%
“…Re cently, studies at the molecular level have shown that a patient with low ASA activity (around 20% of normal controls) with neurological and psychiatric symptoms is a probable MLD/pseudodeficiency compound hetero zygote (ASA"/ASAp) at the ASA locus [31]. This possi bility must also be considered in psychiatric cases for which only ASA has been determined and been found low [32,33]; it is still controversial to what extent low ASA activity, not related to MLD itself, predisposes for neurological and psychiatric symptomatology [28,31,34], or whether it is coincidental [35,36].…”
Section: Biochemical Diagnosismentioning
confidence: 99%